2017
DOI: 10.17222/mit.2016.259
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the thermal fatigue resistance for 3.1C, 0.8Si, 0.9Mn, 1.7Cr, 4.5Ni and 0.3Mo ICDP cast iron roll at 600 °C

Abstract: Using a new test rig the characteristics related to the thermal fatigue resistance for ICDP (Indefinite Chill Double Pour) cast iron for hot working rolls was investigated. Tests were carried out at 600°C to obtain the characteristics of cracks at (500, 1000 and 1500) cycles. For comparative purposes, additionally a test at 500°C was carried out. The average length of all the cracks, their density, average length of five longest cracks and relevant microstructural characteristics for the mentioned cycles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this context, in addition to the presence of carbides and their network distribution, the percentage of graphite and its morphology also play a very important role against said thermal cycling. Although crack nucleation is predominant in carbides, the subsequent progression of cracks may be favored by laminar graphite morphologies [9,10]. However, thermal conductivity is improved by this morphology compared to compact and spheroidal morphologies [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, in addition to the presence of carbides and their network distribution, the percentage of graphite and its morphology also play a very important role against said thermal cycling. Although crack nucleation is predominant in carbides, the subsequent progression of cracks may be favored by laminar graphite morphologies [9,10]. However, thermal conductivity is improved by this morphology compared to compact and spheroidal morphologies [11].…”
Section: Introductionmentioning
confidence: 99%
“…A study has found that most of the cracks originate from the sharp corners of the carbide end [3]. Therefore, under the premise that without reducing the number of carbides to ensure wear resistance, one of the main ways to improve the performance of rolls is to reduce the occurrence of cracks and spalling by modifying the morphology of carbides [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The presence graphite increases resistance to thermal shock. At the same time, the graphite perfor functions of dry lubrication, thus reducing the coefficient of friction between the roll a the sheet of steel [4,[14][15][16][17][18]. The aim of this study is to identify those manufacturing factors which have a sig icant effect on resistance to wear on the work layer.…”
Section: Introductionmentioning
confidence: 99%